Tujuan dan Ruang Lingkup Pendidikan Islam: Studi Komparatif Tafsir Surat Al-Baqarah Ayat 62 dan An-Nur Ayat 55 - Achmad, Syaefudin (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2022)
One aspect of Islamic education is the purpose and scope of Islamic education. There are several verses of the Koran which contains the theme of the purpose and scope of Islamic education, including the letter al-Baqarah verse 62 as well as an-Nur verse 55. One method to interpret the verse is the method muqaran (comparative). Both texts are compared against each other to find a common thread. Of those verses can be concluded that the purpose of Islamic education is to achieve the happiness of living in the world and the hereafter and the scope of Islamic education are the efforts to achieve the objectives of Islamic education (happiness in this world and the Hereafter) which includes faith in God and do good pious